Evaluation of Administrative Position Equalization Policy Into Functional Positions at the Institute of Home Government - Indriyani, Indriyani; Fernandes Simangunsong; Eva Eviany (INFOKUM, 2025)
Bureaucratic simplification is part of the national bureaucratic reform that aims to create an effective, efficient, and professional government. One form of implementation is the equalization of administrative positions into functional positions. In the Institute of Domestic Government, this policy began to be implemented in 2020 by equalizing 137 administrative positions into functional positions. However, many functional officials resulting from the equalization still have difficulty in carrying out their new duties. This study aims to evaluate the implementation of the policy of equalizing administrative positions into functional positions at IPDN. In addition, this study also identifies supporting factors, obstacles, and efforts made to overcome them using a qualitative approach and the CIPP (Context, Input, Process, Product) evaluation model developed by Stufflebeam. Data were collected through in-depth interviews, observations, and documentation, and analyzed using NVivo software. The evaluation results show that this policy has a strong foundation and supports the bureaucratic reform agenda and is relevant to IPDN's objectives, but still faces challenges in the input aspect, such as limited resources, lack of training, and inadequate work guidelines. In terms of process, policy implementation is hampered by weak coordination between units, minimal monitoring and evaluation, and low employee involvement in decision making. Although in the evaluation of this policy product it has a positive impact on employee professionalism and satisfaction, the effectiveness of its implementation is still not optimal due to mismatched tasks and increasing administrative burdens.